A thermal conductive composite phase change material with enhanced volume resistivity by introducing silicon carbide for battery thermal management. (5th November 2018) - Yuan, Wangzhou; Yang, Xiaoqing; Zhang, Guoqing; Li, Xinxi
Highlights: A new kind of SiC-enhanced composite phase change material (CPCM) is prepared. Introducing the SiC component can enhance the mechanical strength of the CPCM. SiC increases the thermal conductivity but reduces the electrical conductivity. SiC-enhanced CPCM shows better cooling performance compared to that without SiC. Abstract: Conventional strategy to enhance the thermal conductivity of the composite phase change material (CPCM) may raise another neglected safety issue in practical applications of battery thermal management (BTM): the electrical conductivity of the CPCM module is significantly increased due to the addition of the conductive carbonaceous or metallic component. To address this issue, we develop a new kind of CPCM herein by introducing a silicon carbide (SiC)/expanded graphite thermal conductive skeleton. The high thermal conductivity and electrical resistivity of the SiC endow the obtained CPCM with a high thermal conductivity but low electrical conductivity. For example, after adding 15 wt% of SiC, the volume resistivity of the CPCM is increased from 4.9 to 12.5 × 10 11 Ω cm, whereas the corresponding thermal conductivity is increased from 1.1 to 2.0 W m −1 K −1, thus giving rise to a much better cooling performance for BTM, especially under high discharge rate. Furthermore, adding a suitable amount of the SiC will also enhance the mechanical strength, which is beneficial to the practical application.